Dual Inhibition of MEK and PI3K Pathway in KRAS and BRAF Mutated Colorectal Cancers - Temraz, Sally (Int J Mol Sci, 2015)
Colorectal cancer (CRC) is a heterogeneous disease with multiple underlying causative genetic mutations. Genetic mutations in the phosphatidylinositol-3 kinase (PI3K) and the mitogen activated protein kinase (MAPK) pathways are frequently implicated in CRC. Targeting the downstream substrate MEK in these mutated tumors stands out as a potential target in CRC. Several selective inhibitors of MEK have entered clinical trial evaluation; however, clinical activity with single MEK inhibitors has been rarely observed and acquired resistance seems to be inevitable. Amplification of the driving oncogene KRAS(13D), which increases signaling through the ERK1/2 pathway, upregulation of the noncanonical wingless/calcium signaling pathway (Wnt), and coexisting PIK3CA mutations have all been implicated with resistance against MEK inhibitor therapy in KRAS mutated CRC. The Wnt pathway and amplification of the oncogene have also been associated with resistance to MEK inhibitors in CRCs harboring BRAF mutations. Thus, dual targeted inhibition of MEK and PI3K pathway effectors (mTOR, PI3K, AKT, IGF-1R or PI3K/mTOR inhibitors) presents a potential strategy to overcome resistance to MEK inhibitor therapy. Many clinical trials are underway to evaluate multiple combinations of these pathway inhibitors in solid tumors.